Imaging Through Random Scatterer with Spatial Coherence Structure Measurement - Peng, Deming; Zhang, Xuan; Liu, Yonglei; Zhu, Yimeng; Chen, Yahong; Wang, Fei; Cai, Yangjian (Frontiers in Physics, 2022)
Optical coherence is becoming an efficient degree of freedom for light field manipulations and applications. In this work, we show that the image information hidden a distance behind a random scattering medium is encoded in the complex spatial coherence structure of a partially coherent light beam that generates after the random scatterer. We validate in experiment that the image information can be well recovered with the spatial coherence measurement and the aid of the iterative phase retrieval algorithm in the Fresnel domain. We find not only the spatial shape but also the position including the lateral shift and longitudinal distances of the image hidden behind the random scatterer can be reconstructed, which indicates the potential uses in three-dimensional optical imaging through random scattering media.